Study of the content of unsaturated fatty acids in seeds of Tagetes erecta L. var. «Albatros» - Maliuhina, O. O.; Smoilovska, H. P.; Малюгіна, Олена Олександрівна; Смойловська, Галина Павлівна (Warsaw : Sp. z o. o. "iScience", 2020)
Annotation. The paper considers the results of a study of the content fatty acids in the vegetable plant raw materials (seeds) Tagetes erecta L. var. «Albatros». The fatty acid content was determined by gas chromatography. The quantitative content of fatty acids was determined by the method of internal normalization, taking the sum of the areas of all peaks for 100%. As a result of the experiment, it was found that in the seeds of Tagetes erecta L. var. «Albatros» are dominated by polyunsaturated fatty acids. The main unsaturated fatty acids of the studied vegetable plant material are linolenic (up to 35.970 ± 1.799%) and linoleic (up to 26.492 ± 1.325%) acids.
Keywords: Tagetes erecta L.; fatty acids; unsaturated fatty acids; marigold; seeds